TRANSLATOR’S EDUCATIONAL PERSPECTIVE IN ACCESSION COUNTRY - Seljan, Sanja; Kučiš, Vlasta (2011)
Education for translator’s profession requires not only, language knowledge skills, but also intercultural communication, use of ICT, terminology work, project management, translation theory and language culture, as defined by the European Master’s Translation (EMT) which combines different teaching methods. Educational university programmes should adopt new educational and professional requirements at different levels of education. The paper analyses interests among students at the Faculty of Humanities and Social Sciences, University of Zagreb regarding the use of translation technology and need for the development of proper language resources, as well as their interest for future education as translator’s specialist. The results are compared with the real situation among translators in Croatia regarding their use of translation technology and their need for professional specialization.
Projekt MZOS
ENG